Mechanisms of Electroacupuncture-Induced Analgesia on Neuropathic Pain in Animal Model - Kim, Woojin (Hindawi Publishing Corporation, 2013)
Neuropathic pain remains as one of the most difficult clinical pain syndromes to treat. Electroacupuncture (EA), involving endogenous opioids and neurotransmitters in the central nervous system (CNS), is reported to be clinically efficacious in various fields of pain. Although multiple experimental articles were conducted to assess the effect of EA-induced analgesia, no review has been published to assess the efficacy and clarify the mechanism of EA on neuropathic pain. To this aim, this study was firstly designed to evaluate the EA-induced analgesic effect on neuropathic pain and secondly to guide and help future efforts to advance the neuropathic pain treatment. For this purpose, articles referring to the analgesic effect of acupuncture on neuropathic pain and particularly the work performed in our own laboratory were analyzed. Based on the articles reviewed, the role of spinal opioidergic, adrenergic, serotonergic, cholinergic, and GABAergic receptors in the mechanism of EA-induced analgesia was studied. The results of this research demonstrate that μ and δ opioid receptors, α (2)-adrenoreceptors, 5-HT(1A) and 5-HT(3) serotonergic receptors, M(1) muscarinic receptors, and GABA(A) and GABA(B) GABAergic receptors are involved in the mechanisms of EA-induced analgesia on neuropathic pain.